PENGARUH INFORMASI AKUNTANSI TERHADAP RETURN SAHAM: PERTIMBANGAN UKURAN PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Edo Setiawan; Rochmawati Daud (AKUNTABILITAS, 2012)
This research investigates six financial ratios (CR, DER, TAT, ROE, EPS, BVS) asaccounting information that being influence to stock return (measured by averageabnormal return), and how these effect simultanly and partially by considering the firmsize that based on total assets. Investigation is primarily focused on the value relevance ofaccounting information from 125 manufacturing firms at the Jakarta Stock Exchange in2004 and 2005. The t and F tests in multiple regression models are used to test hypotheses.The result of testing show that in 2004 there is no a significant effect but in 2005accounting information only explain stock return variation about 4.3%. Partially,in 2005there are only EPS and BVS have significant value under 10%. Testing by considering thefirm size show that significant value is only showed by third group in 2004 (19.2%) and2005 (17%). Partially, in 2004 and 2005, TAT (third group) inclined to become investor’sattention and other variables show various result.